Structural Insights into the TES/TFA Reduction of Differently Substituted Benzofurans: Dihydrobenzofurans or Bibenzyls? - D’Orsi, Rosarita; Caivano, Ilaria; Funicello, Maria; Lupattelli, Paolo; Chiummiento, Lucia (Synlett, 2020)
Various polysubstituted benzofurans were reduced by using triethylsilane in trifluoracetic acid. 2,3-Dihydrobenzofurans or bibenzyl compounds were obtained in high yields, depending on the nature of the substituents at C2 and on the benzene ring of the core structure. A p-anisole substituent at C2 of benzofurans always led to the corresponding bibenzyls.
Keywords: benzofurans; dihydrobenzofurans; bibenzyls; triethylsilane; trifluoroacetic acid; reduction